STEROIDS AND TRITERPENOIDS IN ACACIA CATECHU BARK EXTRACTS: A COMPARATIVE STUDY AND BIBLIOGRAPHIC ANALYSIS - TIWARI, ARCHANA; TIWARI, AVINASH (International Journal of Current Pharmaceutical Research, 2024)
Objective: Plant-derived steroids and triterpenes have been recognized for a number of health benefits. As indicated in previous research, some of the phytosterols are essential dietary substances. This study was aimed at investigating the presence or absence of these phytochemicals in various test bark extracts from Acacia catechu plant samples. Methods: For this study, thirty samples of test plants were gathered in various seasons from the research location. Six different solvents were then prepared for each sample. Then the qualitative tests of the studied parameters were done using various standardized methods. Additionally, bibliographic analysis was done to validate and co-relate the present study with earlier findings. Results: Results showed the presence of test parameters in all solvent systems except aqueous extracts, though the colour intensity (quantity) was different in all other extracts. Based on the dark-colored reaction mixture, it can be claimed that the steroid and triterpene content was relatively higher in methanolic and ethanolic extracts. The comparative bibliographic study was also validating the beneficial applications of the same. Conclusion: Possibly, this preliminary study helped to find out the medicinal significance of native flora of Guna district and also serve as the base for further investigations.